Positive electrode active material, method for preparing same, positive electrode, and rechargeable lithium battery
By coating aluminum and titanium on the surface of the lithium nickel-manganese composite oxide positive electrode active material, a positive electrode active material with excellent capacity and efficiency characteristics is formed, and the problem of insufficient cobalt supply in the prior art is solved, and the performance of lithium battery with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202411530623.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, the positive electrode active substance of a rechargeable lithium battery with high energy density contains rare metal cobalt, which is insufficient supply and high cost, making it difficult to develop high-efficiency positive electrode active substances that do not contain cobalt or reduce cobalt content.
A positive electrode active material with excellent capacity and efficiency characteristics are formed by preparing a plurality of core particles and coating solutions using a positive electrode active material including a layered lithium nickel-manganese composite oxide and containing aluminum (Al) and titanium (Ti) in its surface coating.
High capacity, long cycle life and efficient charging and discharging under high temperature and high voltage conditions are achieved, reducing production costs and reducing dependence on rare metal cobalt.
Smart Images

Figure CN119920865A_ABST
Abstract
Description
Technical Field
[0001] One or more aspects of embodiments of the present disclosure are directed to a positive electrode active material, a method for preparing the same, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. Background Art
[0002] Rechargeable lithium batteries with relatively high energy density and easy portability can be used as driving power sources for portable information devices (such as cellular phones, laptop computers, smart phones, etc.), as driving power sources for hybrid vehicles or electric vehicles (car batteries), and / or as power storage power sources for energy storage systems (ESS) or power walls. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources for hybrid vehicles and / or electric vehicles and / or as power storage power sources.
[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries with desired characteristics for desired uses. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and / or lithium cobalt oxides can be used as positive electrode active materials. However, despite the recent significant increase in demand for large, high-capacity and / or high-energy-density rechargeable lithium batteries, it is expected that the supply of positive electrode active materials containing rare metal cobalt is seriously insufficient (shortage of supply). For example, because cobalt is expensive and there are not many remaining reserves, it is necessary or desirable to develop a suitable positive electrode active material that does not contain cobalt or reduces its content (e.g., amount). Summary of the invention
[0004] One or more aspects of the embodiments of the present disclosure relate to a positive electrode active material including a lithium nickel manganese composite oxide, which includes an optimal or desired coating to improve the performance, capacity characteristics, initial charge / discharge efficiency (hereinafter, also written as "initial charge and discharge efficiency", or simply "efficiency") and / or high temperature cycle life characteristics of a rechargeable lithium battery at high temperature and high voltage.
[0005] In some embodiments, the positive electrode active material includes: a plurality of core particles comprising a layered lithium nickel manganese-based composite oxide, wherein the nickel content (e.g., amount) is greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese-based composite oxide; and a coating layer located on the surface of each of the plurality of core particles and containing aluminum (Al) and titanium (Ti).
[0006] In some embodiments, a method for preparing a positive electrode active material includes (i) preparing a plurality of core particles comprising a layered lithium nickel manganese composite oxide, wherein the nickel content (e.g., amount) is greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, (ii) adding an aluminum raw material and a titanium raw material to an aqueous solvent and mixing them to prepare a coating solution, (iii) adding a plurality of core particles to the coating solution and mixing them to prepare a mixed solution, and (iv) removing the aqueous solvent from the mixed solution, drying the resulting product, and performing a heat treatment to obtain a positive electrode active material.
[0007] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material of the present embodiment.
[0008] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, negative electrode, and electrolyte.
[0009] The positive electrode active material according to some embodiments can maximize or increase capacity while minimizing or reducing production costs, can ensure or improve long cycle life characteristics and improve high voltage characteristics and high temperature characteristics. If (for example, when) the positive electrode active material is applied to a rechargeable lithium battery, a relatively high initial charge / discharge capacity and efficiency can be achieved under high voltage operating conditions, and long cycle life characteristics can be achieved under high voltage and high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 to Figure 4 are schematic diagrams each showing a rechargeable lithium battery according to some embodiments.
[0011] Figure 5 is a scanning electron microscope (SEM) image of the surface of the coating product prepared in Example 1.
[0012] Figure 6 To highlight Figure 5 EDS (energy dispersive X-ray spectroscopy) analysis image of the Al element in.
[0013] Figure 7 To highlight Figure 5 EDS analysis image of Ti element in.
[0014] Figure 8 is a SEM image of the surface of the coated product of Example 1.
[0015] Fig. 9 To highlight Figure 8 EDS analysis image of the Al element in the white square area.
[0016] Fig.10 To highlight Figure 8 EDS analysis image of the Ti element in the white square area.
[0017] Fig.11 for Figure 8 to Figure 10 EDS analysis of region 2 is shown in FIG.
[0018] Fig.12 and Fig.13 is a SEM image of the surface of the final positive electrode active material prepared in Example 1.
[0019] Fig.14 and Fig.15 is a SEM image of the surface of the final positive electrode active material prepared in Comparative Example 1.
[0020] Fig.16 Graph showing the results of X-ray photoelectron spectroscopy (XPS) on the surface of the final positive electrode active material of Example 1, showing an enlarged peak at a position where Al is exhibited.
[0021] Fig.17 This is a graph showing the results of XPS analysis on the surface of the final positive electrode active material of Example 1, showing an enlarged peak at a position where Ti is exhibited.
[0022] Fig.18 This is an XPS depth distribution analysis diagram of the final positive electrode active material of Example 1.
[0023] Fig.19 For single display only Fig.18 Curve graph of the distribution of Al element and Ti element in the sample.
[0024] Description of Reference Numerals
[0025] 100: Rechargeable lithium battery 10: Positive electrode
[0026] 11: Positive electrode lead lug 12: Positive electrode terminal
[0027] 20: Negative electrode 21: Negative electrode lead lug
[0028] 22: Negative electrode terminal 30: Separator
[0029] 40: electrode assembly 50: shell
[0030] 60: Sealing member 70: Electrode terminal piece
[0031] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION
[0032] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0033] The terms used herein are for describing the embodiments only and are not intended to limit the present disclosure. A singular expression includes a plural expression unless the context clearly indicates otherwise.
[0034] As used herein, "combinations thereof" refers to mixtures, stacks, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0035] In this document, it should be understood that terms such as "comprises," "includes," or "has" are intended to indicate the presence of implemented features, quantities, steps (e.g., actions or tasks), elements, or a combination thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps (e.g., actions or tasks), elements, or a combination thereof.
[0036] In the drawings, the thickness of layers, films, panels, regions, etc. are exaggerated for clarity, and the same reference numerals represent the same elements throughout, and repeated descriptions thereof may not be provided in the specification. It will be understood that if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element, it may be directly on the other element or there may also be intervening elements. In contrast, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements.
[0037] In one or more embodiments, the “layer” herein includes not only a shape formed on the entire surface but also a shape formed on a partial surface if (for example, when) viewed from a plan view.
[0038] The average particle size can be measured by any suitable method in the art (e.g., by a particle size analyzer, by a transmission electron microscope image and / or a scanning electron microscope image). In one or more embodiments, the average particle size value is obtained by using a dynamic light scattering method (e.g., by using a measuring device with dynamic light scattering), performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise defined, the average particle size (D 50 ) may refer to the diameter of particles that have a cumulative volume of 50% by volume in a particle size distribution. If (for example, when) no additional definition is provided, the average particle size (D 50) refers to the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters of spherical particles or lengths of the major axes of non-spherical particles) of about 20 particles in a scanning electron microscope image.
[0039] In this document, "or" is not to be interpreted as an exclusive meaning, for example, "A or B" is to be interpreted as including A, B, A+B, etc. Further, expressions such as "at least one of...", "one of...", and "selected from...", as used herein, when preceding or following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, "selected from at least one of a, b, and c" and "at least one of a, b, and c" may indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all a, b, and c, or variations thereof.
[0040] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0041] Further, when describing embodiments of the present disclosure, the use of “may” refers to “one or more embodiments of the present disclosure.”
[0042] The term "metal" is interpreted as a concept including common metals, transition metals and metalloids (semimetals).
[0043] As used herein, the terms "use," "using," and "used" may be considered synonymous with the terms "utilize," "utilizing," and "utilized," respectively.
[0044] For ease of description, spatially relative terms, such as "below," "beneath," "below," "above," "up," "bottom," "top," etc., may be used herein to describe the relationship of one element or feature to another element or feature illustrated in the accompanying drawings. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation depicted in the accompanying drawings. For example, if the device in the figure is turned over, elements described as being "below" or "beneath" other elements or features would then be oriented "above" or "on" the other elements or features. Thus, the term "below" may encompass both orientations of above and below. The device may be otherwise oriented (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0045] As used herein, the terms "substantially," "about," and the like are used as approximate terms and not as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that one of ordinary skill in the art will recognize. As used herein, the terms "about" or "approximately" include the stated value and mean within an acceptable range of deviations of the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0046] Any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision falling within the range set forth. For example, the range of "1.0 to 10.0" is intended to include between the minimum value 1.0 set forth and the maximum value 10.0 set forth (and including 1.0 and 10.0), that is, all sub-ranges with a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit set forth in this article is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth herein.
[0047] The battery management system and / or any other related device or component according to the embodiments of the present disclosure described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as, for example, a random access memory (RAM)). The computer program instructions may also be stored in other non-temporary computer-readable media, such as, for example, a CD-ROM or a flash drive, etc. Moreover, those skilled in the art should recognize that, without departing from the scope of the embodiments of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed on one or more other computing devices.
[0048] Positive electrode active material
[0049] In some embodiments, the positive electrode active material includes: a plurality of core particles comprising a layered lithium nickel manganese composite oxide, wherein the nickel content (e.g., amount) is greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide; and a coating located on the surface of each of the plurality of core particles and containing Al and Ti.
[0050] Since the price of rare metal cobalt has risen sharply recently, it is necessary (or desirable in the art) to develop a positive electrode active material that does not contain cobalt or reduces its content (e.g., amount). Among them, positive electrode active materials with olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium iron manganese phosphate (LMFP), etc.), or positive electrode active materials with spinel crystal structure (such as lithium manganese oxide (LMO), etc.), due to the small amount of lithium available in the structure (e.g., low), have limitations in achieving appropriate high capacity. Due to the appropriate high lithium capacity available in the structure, layered lithium nickel manganese positive electrode active materials have excellent or appropriate capacity and efficiency characteristics, making them suitable as materials for high-capacity batteries. However, when cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it becomes difficult to ensure long cycle life characteristics. In addition, layered lithium nickel manganese positive electrode active materials that do not contain cobalt may have the problem of accelerating side reactions with the electrolyte under high voltage and high temperature conditions, thereby resulting in an increase in gas generation and deterioration of cycle life characteristics.
[0051] In order to improve the surface stability of layered lithium nickel manganese positive electrode active materials in high voltage regions, a method for improving cycle life characteristics by coating the positive electrode active material with elements such as Al can be considered. However, because these coating elements use electrochemically inactive non-transition metal elements, the resistance may increase, and the charge / discharge efficiency may be lower than the charge / discharge efficiency before coating. In some embodiments, a coating including (e.g., simultaneously including) both Al and Ti is introduced onto the surface of a layered lithium nickel manganese positive electrode active material, thereby strengthening the particle surface and forming a coating having a structural 3D lithium channel, thereby improving the cycle life characteristics and initial charge and discharge efficiency under high voltage and / or high temperature operating conditions.
[0052] Nuclear particles
[0053] The core particles include layered lithium nickel manganese composite oxides. Based on the total metals other than lithium in 100mol% of the layered lithium nickel manganese composite oxides, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies any of the above ranges, even if the cobalt content (e.g., amount) is reduced, a suitable high capacity can be achieved, and structural stability can be increased.
[0054] Based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the manganese content (e.g., amount) may be, for example, greater than or equal to about 10 mol% (e.g., about 10 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30%). If the manganese content (e.g., amount) satisfies any of the above ranges, the positive electrode active material can improve structural stability while achieving a suitable high capacity.
[0055] The layered lithium nickel manganese composite oxide may be a layered lithium nickel manganese aluminum composite oxide, which further includes aluminum in addition to nickel and manganese. If the layered lithium nickel manganese composite oxide contains aluminum, it is beneficial to maintain a properly or substantially stable layered structure even if the structure does not contain cobalt. Based on 100 mol% of the total metal other than lithium in the layered lithium nickel manganese composite oxide, the aluminum content (e.g., amount) may be greater than about 0 mol%, greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol% (e.g., greater than about 0 mol% and less than or equal to about 3 mol%, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1.5 mol% to about 2.5 mol%). If the aluminum content (e.g., amount) satisfies any of the above ranges, a properly or substantially stable layered structure can be maintained even without cobalt, the problem of structural collapse due to charging and discharging can be suppressed or reduced, and a long cycle life characteristic of the positive electrode active material can be achieved.
[0056] According to some embodiments, the concentration of aluminum in the core particle can be substantially uniform. For example, there may be a concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration in the outer part of the core particle may be neither higher than nor lower than the aluminum concentration in the inner part of the core particle, and the aluminum in the core particle may be uniformly (or substantially uniformly) distributed. This structure can be obtained by using aluminum raw materials during precursor production, and not additionally doping aluminum during the synthesis process of the core particle, thereby using nickel-manganese-aluminum hydroxide as a precursor to synthesize composite oxides. The core particle may be in the form of a secondary particle in which a plurality of primary particles are gathered, and regardless of the position of the primary particle, the aluminum content (e.g., amount) inside the primary particle can be the same or similar. For example, if the primary particle is selected at a random position in the cross section of the secondary particle, and the aluminum content (e.g., amount) is measured inside the primary particle rather than at its interface, then regardless of the position of the primary particle (e.g., whether the primary particle is close to the center of the secondary particle or close to the surface), the aluminum content (e.g., amount) can be the same / similar / substantially uniform. In this structure, even if cobalt is not present or is present in a very small (e.g., significantly or greatly reduced) amount, a suitably stable layered structure can be maintained and no aluminum byproducts and / or aluminum aggregates are generated, thereby simultaneously (e.g., synchronously) improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.
[0057] The lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1.
[0058] Chemical formula 1
[0059] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 .
[0060] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
[0061] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5 or 0.9 ≤ a1 ≤ 1.2. In some embodiments, Chemical Formula 1 may contain aluminum, in which case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03 and 0 ≤ w1 ≤ 0.29 may be satisfied, or for example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03 and 0 ≤ w1 ≤ 0.29 may be satisfied.
[0062] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8 or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39 or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02 or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1 or 0 ≤ w1 ≤ 0.09.
[0063] For example, the layered lithium nickel manganese composite oxide may not contain cobalt or may contain a small amount of cobalt, and based on the total metals other than lithium in 100 mol% of the layered lithium nickel manganese composite oxide, the cobalt content (e.g., amount) may be about 0 mol% to about 0.01 mol%.
[0064] The core particles may be in the form of secondary particles made by aggregating a plurality of primary particles. The secondary particles may be spherical, elliptical, polyhedral and / or irregular in shape, and the primary particles may be spherical, elliptical, plate-shaped or a combination thereof.
[0065] If (e.g., when) the battery operates under high voltage or high temperature conditions, the core particles are vulnerable to chemical erosion by the components in the electrolyte, and thus may undergo many side reactions with the electrolyte, resulting in an increase in the amount of gas generated, thereby deteriorating the battery cycle life and safety. However, these problems can be solved by introducing a coating according to the present embodiment, and the coating according to the present embodiment will be described in more detail below in this text.
[0066] Coating
[0067] The positive electrode active material according to some embodiments includes a coating located on the surface of the core particles and containing Al and Ti.
[0068] The Al content (e.g., amount) may be about 5 at% to about 35 at%, for example, about 5 at% to about 30 at%, about 5 at% to about 25 at%, about 5 at% to about 20 at%, or about 10 at% to about 20 at%, based on 100 at% of the total elements on the surface of the positive electrode active material as measured by X-ray photoelectron spectroscopy (XPS). In some embodiments, the Ti content (e.g., amount) may be about 0.1 at% to about 3.0 at%, for example, about 0.3 at% to about 2.5 at%, or about 0.5 at% to about 2.0 at%, based on 100 at% of the total elements on the surface of the positive electrode active material as measured by XPS.
[0069] The total elements may be, for example, Li, Ni, Mn, Al, Ti, O, and C. In this article, the Al and Ti contents on the surface may be measured by XPS depth profile analysis. If the Al and Ti contents on the surface of the positive electrode active material satisfy any of the above respective ranges, the initial charge / discharge capacity, initial charge / discharge efficiency, and cycle life characteristics at high temperature and high voltage of a rechargeable lithium battery using the positive electrode active material may be simultaneously (e.g., synchronously) improved.
[0070] In some embodiments, the Al content (e.g., amount) of the coating may be about 0.1 mol% to about 3.0 mol%, for example, about 0.1 mol% to about 2.0 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.7 mol% to about 1.3 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material. The Al content (e.g., amount) of the coating refers to the Al content (e.g., amount) contained only in the coating, and has nothing to do with the Al contained in the core particles. The total metal other than lithium in the positive electrode active material as a reference for the above content (e.g., amount) range refers not to the components on the surface of the positive electrode active material, but to the content (e.g., amount) of all metals (other than lithium) present in the entire positive electrode active material.
[0071] In some embodiments, the Ti content (e.g., amount) of the coating layer may be about 0.01 mol% to about 1.5 mol%, for example, about 0.05 mol% to about 1.0 mol%, about 0.1 mol% to about 1.0 mol%, about 0.1 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material.
[0072] The total amount of Al and Ti in the coating layer may be about 0.11 mol % to about 4.5 mol %, for example, about 0.5 mol % to about 1.5 mol %, based on 100 mol % of the total metals other than lithium in the positive electrode active material. This may refer to the Al and Ti content included only in the coating layer, regardless of the Al and Ti included or possibly included in the core particle.
[0073] The Al and Ti contents in the coating of the entire positive electrode active material can be measured, for example, by SEM-EDS analysis of the surface or cross-section of the positive electrode active material. Therefore, "on the surface of the positive electrode active material, the ratio (Al / Ti) of the Al content (e.g., amount) to the Ti content (e.g., amount) may be greater than or equal to about 2" can be understood as "the ratio (Al / Ti) of the Al content (e.g., amount) of the coating to the Ti content (e.g., amount) of the coating may be greater than or equal to about 2". If the Al and Ti contents in the coating satisfy their respective ranges, the coating may have a substantially uniform and thin thickness, which does not increase (e.g., does not undesirably increase) the resistance of the positive electrode active material, and effectively or appropriately inhibits or reduces side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the Al and Ti contents of the coating are too high (e.g., outside the ranges described above), a suitably uniform coating (e.g., a coating of suitably uniform thickness) may not be formed and / or the resistance may increase, which may reduce the charge / discharge efficiency and cycle life characteristics, and if the aluminum content (e.g., amount) of the coating is too small (e.g., outside the ranges described above), a coating of suitable or appropriate thickness may not be formed, and the effect of suppressing or reducing side reactions with the electrolyte may be reduced.
[0074] On the surface of the positive electrode active material, the ratio (Al / Ti) of the Al content (e.g., amount) to the Ti content (e.g., amount) may satisfy (e.g., may be) greater than or equal to about 2, e.g., about 2 to about 50, about 2 to about 40, about 2 to about 30, about 2 to about 20, about 2 to about 10, or about 3 to about 7. If any of the above ratios is satisfied, the initial charge / discharge capacity, initial charge / discharge efficiency, and cycle life characteristics at high temperature and high voltage of the rechargeable lithium battery may be simultaneously (e.g., synchronously) improved.
[0075] The coating according to some embodiments may be in the form of a film that continuously surrounds the surface of the core particle, or may be in the form of a shell that surrounds the entire surface of the core particle. This is different from a structure that only partially coats a portion of the surface of the core particle. According to some embodiments, the coating may be formed to completely cover (or encapsulate) the surface of the core particle, and may be formed to be very (or appropriately or substantially) thin and substantially uniform in thickness, so the positive electrode active material does not increase resistance or reduce capacity, improve structural stability, effectively or appropriately or substantially inhibit or reduce side reactions with the electrolyte, reduce gas generation under high voltage and high temperature conditions, and achieve long cycle life characteristics.
[0076] In the coating layer, Al and Ti may be mixed together, and Ti may be distributed in a part or the entire region where Al is distributed.
[0077] The coating may have a thickness of about 5 nm to about 200 nm, for example, about 5 nm to about 150 nm, about 5 nm to about 100 nm, about 5 nm to about 80 nm, about 5 nm to about 50 nm, or about 10 nm to about 50 nm. If the coating satisfies any of the above thickness ranges, the structural stability of the positive electrode active material can be improved without increasing (e.g., undesirably increasing) resistance or reducing (e.g., undesirably reducing) capacity due to the coating, and the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced. The thickness of the coating can be measured by, for example, SEM, transmission electron microscopy (TEM), time-of-flight secondary ion mass spectrometry (TOF-SIMS), XPS and / or EDS analysis, and can be measured, for example, by EDS line profile analysis of a cross section of the positive electrode active material.
[0078] The coating according to some embodiments is characterized by having a suitably thin thickness of several nanometers to several hundred nanometers and a substantially uniform thickness. For example, the deviation of the coating thickness in one positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness within one positive electrode active material particle. For example, the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle can be measured to calculate the arithmetic mean, and then the absolute value of the difference between a measured data point and the arithmetic mean is divided by the arithmetic mean, and then multiplied by 100%, to calculate the deviation of the coating thickness. If the deviation and / or standard deviation of the coating thickness meets the above range, a coating with a substantially or appropriately uniform thickness can be formed in the form of a good or appropriate film on the surface of the core particle of the positive electrode active material. Accordingly, the structural stability of the positive active material is improved, the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced, and the undesirable resistance increase or capacity reduction caused by the coating can be minimized or reduced.
[0079] The coating may include layered aluminum compounds, such as aluminum oxide, lithium aluminum oxide (e.g., LiAlO 2 ) or a combination thereof.
[0080] In some embodiments, the coating may include a titanium compound, such as titanium oxide, lithium titanium oxide (e.g., Li 2 TiO 3 ) or a combination thereof. The titanium compound may have a 3D lithium channel, thereby further improving the charging and discharging efficiency of the rechargeable lithium battery.
[0081] In addition to aluminum, the coating may further contain nickel, manganese, or a combination thereof. The average particle size (D) of the positive electrode active material in particle form (i.e., in the form of positive electrode active material particles, the positive electrode active material particles including core particles and a coating on the surface of each core particle) according to some embodiments 50 ) is not particularly limited, but may be (i.e., the average diameter of the particles may be) for example, about 1 μm to about 25 μm, about 5 μm to about 25 μm, about 10 μm to about 25 μm, about 11 μm to about 20 μm, or about 12 μm to about 18 μm. If (e.g., when) no definition is otherwise provided, the average particle size (D) as used herein is 50 ) refers to the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. If the average particle size of the positive electrode active material satisfies any of the above ranges, a suitably high capacity and a suitably long cycle life can be achieved, and it can be advantageous to form a coating according to some embodiments.
[0082] In some embodiments, the positive electrode active material may be characterized as being free of (e.g., excluding) sodium. In some embodiments, sodium ions may be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail below, a core particle having a suitably stable structure and a coating having a substantially uniform thickness may be formed without the use of sodium ions.
[0083] In one or more embodiments, the positive electrode active material according to some embodiments may contain a sulfur (S) component on the surface, which may be caused by (eg, may be derived from) a coating raw material to be described in more detail herein below.
[0084] Method for preparing positive electrode active material
[0085] In some embodiments, the method for preparing a positive electrode active material includes: (i) preparing a plurality of core particles including a layered lithium nickel manganese composite oxide, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the nickel content (e.g., amount) is greater than or equal to about 60 mol%; (ii) adding an aluminum raw material and a titanium raw material to an aqueous solvent and mixing to prepare a coating solution; (iii) adding a plurality of core particles to the coating solution and mixing to prepare a mixed solution; and (iv) removing the aqueous solvent from the mixed solution, drying the resulting product, and performing a heat treatment to obtain a positive electrode active material. The positive electrode active material according to the present embodiment can be prepared by this method.
[0086] The layered lithium nickel manganese composite oxide can be prepared, for example, by mixing a nickel manganese hydroxide and a lithium raw material and performing a first heat treatment. The nickel manganese composite hydroxide can be a precursor of the core particles and can be in the form of secondary particles in which a plurality of primary particles are aggregated. The nickel manganese composite hydroxide can be prepared by an appropriate coprecipitation method.
[0087] Based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the content of nickel (e.g., amount) can meet the range of greater than or equal to about 60mol%, and can be, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When the nickel content (e.g., amount) meets any of the above ranges, even if the cobalt content (e.g., amount) is reduced, a suitable high capacity can be achieved and structural stability can be increased.
[0088] Based on 100 mol % of the total metals in the nickel-manganese composite hydroxide, the manganese content (e.g., amount) may be greater than or equal to about 15 mol %, for example, about 15 mol % to about 40 mol %, about 15 mol % to about 39 mol %, about 15 mol % to about 35 mol %, about 15 mol % to about 30 mol %, or about 20 mol % to about 30 mol %, etc.
[0089] In one or more embodiments, if (for example, when) the nickel-manganese composite hydroxide further contains aluminum, then based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the aluminum content (for example, amount) may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol% (for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%). If the manganese content and aluminum content of the nickel-manganese composite hydroxide meet any of their respective above-mentioned ranges, a suitable high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0090] In the method for preparing a positive electrode active material according to some embodiments, in the preparation of the core particles, aluminum is not additionally doped, but an aluminum raw material can be used to prepare a precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (e.g., substantially uniformly) dispersed in the structure can be used as a precursor. When such a precursor is used, even without cobalt, even after repeated charging and discharging, the positive electrode active material can stably or appropriately maintain a layered structure, and undesirable aluminum byproducts and / or aluminum aggregates are not formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.
[0091] Based on 100 mol% of the total metals in the nickel-manganese composite hydroxide, the cobalt content (e.g., amount) in the nickel-manganese composite hydroxide may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%. The nickel-manganese composite hydroxide may be said to be economical because it avoids or reduces the increase in unit cost caused by adding cobalt (i.e., it uses greatly reduced or no cobalt), maximizes or increases capacity, and improves structural stability.
[0092] For example, the nickel-manganese-based composite hydroxide can be represented by Chemical Formula 2.
[0093] Chemical formula 2
[0094] Ni x2 Mn y2 Al z2 M 2 w2 (OH) 2 .
[0095] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2It may be one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.
[0096] In Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0097] The nickel-manganese composite hydroxide may be in the form of particles, and the average particle size (D 50 ) may be about 1 μm to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm.
[0098] The nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The first heat treatment may be carried out in an oxygen atmosphere, for example, at a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C, for about 2 hours to about 20 hours or about 4 hours to about 12 hours. The layered lithium nickel manganese composite oxide can be obtained by the first heat treatment. The obtained layered lithium nickel manganese composite oxide is substantially the same as the layered lithium nickel manganese composite oxide described in conjunction with the core particles of the positive electrode active material of the present embodiment.
[0099] Because layered lithium nickel manganese composite oxides and oxides of other compositions (e.g., lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, lithium cobalt oxides, etc.) have significantly different residual lithium contents on the particle surface and have different properties, it is impossible (or difficult) to form a satisfactory or appropriate coating in the form of a substantially uniform film using conventional coating methods. In some embodiments, a method is provided for coating the surface of layered lithium nickel manganese composite oxide particles with Al and Ti in a very (e.g., substantially) uniform thickness.
[0100] In some embodiments, a coating solution is first prepared by adding an aluminum raw material and a titanium raw material to an aqueous solvent and mixing them, and then the core particles are added to the coating solution and mixed. This is a salt dissolution wet coating method and can be referred to as a pre-addition method, in which the salt (e.g., aluminum salt and / or titanium salt) as the coating raw material is first completely dissolved, and then the core particles of the positive electrode active material are added.
[0101] The aqueous solvent may include distilled water, an alcohol solvent, or a combination thereof.
[0102] For example, the aluminum raw material may be aluminum sulfate. Aluminum sulfate may be an optimal or appropriate raw material for forming a substantially uniform coating layer containing Al on the layered lithium nickel manganese-based composite oxide.
[0103] The titanium raw material may be titanium sulfate, titanium nitrate or a combination thereof.
[0104] Based on 100 mol% of the total metals other than lithium in the positive electrode active material (which includes: the total metals other than lithium in the lithium nickel manganese composite oxide, the aluminum of the aluminum raw material, and the titanium of the titanium raw material), the Al content (e.g., amount) in the aluminum raw material can be designed to be about 0.1 mol% to about 3.0 mol%, for example, about 0.1 mol% to about 2.0 mol%, about 0.5 mol% to about 1.5 mol%, about 0.6 mol% to about 1.4 mol%, about 0.7 mol% to about 1.3 mol%, or about 0.8 mol% to about 1.2 mol%. If the Al content (e.g., amount) of the coating is designed within any of the above ranges, the coating can be formed to have a suitably thin thickness of several nanometers to several hundred nanometers and a substantially uniform thickness, thereby reducing the amount of gas generated by the rechargeable lithium battery under high voltage and / or high temperature operating conditions, and improving high capacity and long cycle life characteristics.
[0105] Based on 100 mol% of the total metals other than lithium in the positive electrode active material (which includes: the total metals other than lithium in the lithium nickel manganese composite oxide, the aluminum of the aluminum raw material, and the titanium of the titanium raw material), the Ti content (e.g., amount) in the titanium raw material can be designed to be about 0.01 mol% to about 1.5 mol%, for example, about 0.05 mol% to about 1.0 mol%, about 0.1 mol% to about 1.0 mol%, about 0.1 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. If the Ti content (e.g., amount) of the coating is designed within any of the above ranges, the coating can be formed to have a suitably thin thickness of several nanometers to several hundred nanometers and a substantially uniform thickness to improve cycle life characteristics under high voltage and / or high temperature operating conditions and increase initial charge and discharge efficiency.
[0106] The aluminum raw material and the titanium raw material are added to the aqueous solvent and mixed for about 1 minute to about 60 minutes, for example, about 1 minute to about 30 minutes, about 3 minutes to about 30 minutes, or about 5 minutes to about 10 minutes. In some embodiments, the mixing speed may be about 100rpm to about 800rpm, for example, about 200rpm to about 600rpm or about 250rpm to about 500rpm. Under these conditions, the aluminum raw material and the titanium raw material are completely or appropriately dissolved in the aqueous solvent to obtain a colorless and transparent coating solution, and according to some embodiments, the coating solution can be used to effectively or appropriately form a substantially uniform coating. The pH of the mixed coating solution may be, for example, about 1.5 to about 4, for example, about 2.0 to about 3.5, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2.
[0107] When the core particles are added to the prepared coating solution, the core particles are added thereto while the coating solution is stirred (ie, mixed) to increase the coating quality.
[0108] In one or more embodiments, the time spent adding the core particles to the coating solution may be about 30 seconds / about 500g to about 2 minutes / about 500g, for example, about 30 seconds / about 500g to about 1.5 minutes / about 500g, etc. The speed of adding the core particles can be suitably or appropriately adjusted to control the pH of the supernatant after the coating is completed, so as to induce effective or appropriate formation of a substantially uniform coating according to some embodiments. If the speed of adding the core particles is too low, the reaction rate of each particle will change, and a substantially uniform coating may not be formed. In some embodiments, if the speed of adding the core particles is too fast, the pH may change rapidly (e.g., undesirable rapid changes), and a substantially uniform coating may not be formed.
[0109] After the core particles are all added to the coating solution, stirring can be performed for about 15 minutes to about 60 minutes (e.g., about 20 minutes to about 50 minutes or about 30 minutes to about 45 minutes). From the beginning of adding the core particles to the coating solution to the time spent for stirring (i.e., coating reaction time) can be adjusted in about 1 hour.
[0110] In some embodiments, if (for example, when) the addition of the core particles to the coating solution and mixing are stopped, the pH of the supernatant after the mixing is completed may range from about 5.5 to about 8.5, for example. If the pH of the supernatant is less than 5.5, the acidity may become inappropriately strong acidity and a substantially uniform coating may not be formed, and if the pH is greater than 8.5, the alkalinity may become inappropriately strong alkalinity, making it difficult to form a substantially uniform Al-containing coating.
[0111] After removing the aqueous solvent from the mixed solution, the resulting product can be dried, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C and, for example, under vacuum conditions, and a satisfactory or appropriate coating product can be obtained under these conditions.
[0112] The dried product after removing the aqueous solvent from the mixed solution can be referred to as a coating product. The coating product includes a core particle and a coating located on the surface of the core particle and containing Al and Ti. For example, the coating containing Al and Ti may include a fiber shape (e.g., in the form of fibers), for example, a grid shape and / or a spiderweb shape. This grid can be continuously formed throughout the entire surface of the core particle. The grid shape coating can be very thin or appropriately thin and substantially uniform around the core particle to strengthen the surface of the positive electrode active material and improve structural stability, thereby enhancing high temperature and high voltage characteristics.
[0113] After mixing the nickel-manganese-based composite hydroxide and the lithium raw material, the heat treatment of this mixture may be referred to as a first heat treatment, and the heat treatment of the coated product may be referred to as a second heat treatment.
[0114] In some embodiments, the second heat treatment temperature may be in the range of about 730° C. to about 800° C., for example, about 740° C. to about 800° C., about 750° C. to about 800° C., about 750° C. to about 780° C., or about 750° C. to about 775° C. If the second heat treatment temperature is set to any of the above ranges, the tendency of aluminum to diffuse into the secondary particles may be reduced, and aluminum may be mainly retained on the surface of the secondary particles, and at the same time (for example, synchronously), the surface of the secondary particles may be coated in the form of a very thin or appropriately thin and substantially uniformly thick shell, and titanium may also be well or appropriately coated on the surface of the secondary particles.
[0115] If the second heat treatment temperature exceeds about 800°C, the tendency (e.g., concentration) of aluminum diffusion into the secondary particles increases, making it difficult to form a high-concentration aluminum-rich coating on the surface, and accordingly, the initial charge / discharge capacity and efficiency characteristics at high voltage may be reduced, and the cycle life characteristics under high voltage and high temperature conditions may be reduced. If the second heat treatment temperature is less than about 730°C, a portion of the aluminum and / or titanium may be gathered (e.g., aggregated) and / or unevenly distributed on the surface of the secondary particles, which may result in reduced cycle life characteristics under high temperature and high voltage conditions, and may result in reduced initial charge / discharge efficiency.
[0116] The second heat treatment may be performed, for example, in an oxygen atmosphere for about 2 hours to about 20 hours or about 3 hours to about 10 hours.
[0117] The obtained positive electrode active material includes: a plurality of core particles, which include a layered lithium nickel manganese composite oxide, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the nickel content (e.g., amount) is greater than or equal to about 60 mol%; and a coating layer, which is located on the surface of the core particles and contains Al and Ti. At this time, the coating layer may include a layered aluminum compound and a titanium compound.
[0118] Positive electrode
[0119] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material according to the present embodiment. In addition to the positive electrode active material of the present embodiment, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In some embodiments, the positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.
[0120] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In some embodiments, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. When the positive electrode active material according to some embodiments is applied, it is beneficial to achieve such a loading level and density of the positive electrode active material layer, and the positive electrode satisfying the loading level and density of the positive electrode active material layer within the above range is suitable for realizing a high-capacity, high-energy-density rechargeable lithium battery.
[0121] Binder
[0122] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin or nylon, but are not limited thereto.
[0123] Conductive Materials
[0124] A conductive material (e.g., an electronic conductor) is included to provide electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes chemical changes in the battery (e.g., undesirable chemical changes). Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0125] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer.
[0126] The positive electrode current collector may include an Al foil, but the present disclosure is not limited thereto.
[0127] Rechargeable lithium battery
[0128] Some embodiments provide a rechargeable lithium battery including the positive electrode of the present embodiment, a negative electrode, and an electrolyte. As an example, the rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.
[0129] According to the shape, the rechargeable lithium battery can be classified into a cylindrical battery, a prismatic battery, a pouch battery, a coin battery, etc. Figure 1 to Figure 4 are schematic diagrams each showing a rechargeable lithium battery according to some embodiments, wherein Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, Figure 3 and Figure 4 Each shows a pouch-shaped battery. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20; and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. In some embodiments, Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4As shown in , the rechargeable lithium battery 100 includes electrode tabs 70, which include, for example, a positive electrode tab 71 and a negative electrode tab 72, each of which serves as an electrical path for guiding current formed in the electrode assembly 40 to the outside.
[0130] According to some embodiments of the rechargeable lithium battery, it can be recharged at a high voltage (e.g., under high voltage conditions) and / or can be suitable for driving at a high voltage. For example, the upper charging limit voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, about 4.45V to about 4.55V, etc. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when (e.g., when) charged at a high voltage, and can achieve appropriate high capacity and long cycle life characteristics.
[0131] Negative electrode
[0132] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector and including a negative electrode active material, and the negative electrode active material layer may further include a binder, a conductive material, and / or a combination thereof.
[0133] Negative electrode active material
[0134] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.
[0135] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. The crystalline carbon may have an amorphous shape, or may be natural graphite and / or artificial graphite in the form of flakes, sheets, spheres, and / or fibers. The amorphous carbon may be soft carbon, hard carbon, a mesophase pitch carbonization product, calcined coke, and the like.
[0136] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0137] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0 < x ≤ 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and / or combinations thereof) or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO x (0 < x ≤ 2) (for example, SnO 2 ), Sn alloy, or a combination thereof.
[0138] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles can be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be present in a dispersed state in the amorphous carbon matrix.
[0139] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can contain a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon can include soft carbon, hard carbon, mesophase pitch carbonized products, calcined coke, etc.
[0140] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon can be about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, then based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon can be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon can be about 20 wt% to about 40 wt%.
[0141] In some embodiments, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle size (D 50) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy and / or in an oxidized form of silicon. The oxidized form of silicon may be composed of SiO x (0<x≤2) represents. At this time, the atomic content (eg, amount) ratio of Si:O (which indicates the degree of oxidation) may be about 99:1 to about 33:67. If (eg, when) no additional definition is provided, the average particle size (D) as used herein is 50 ) indicates the diameter of particles where the cumulative volume in the particle size distribution is about 50 volume %.
[0142] The Si-based negative electrode active material and / or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material and / or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed, the mixing ratio may be about 1:99 to about 90:10 by weight.
[0143] Binder
[0144] The binder is used to bind the negative electrode active material particles well or appropriately to each other and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder or a combination thereof.
[0145] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0146] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or a combination thereof.
[0147] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and an alkali metal salt thereof may be used in combination. The alkali metal may be Na, K and / or Li.
[0148] The dry binder may be a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, a polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0149] Conductive Materials
[0150] A conductive material is included to provide electrode conductivity, and any suitable conductive material can be used as the conductive material unless it causes chemical changes in the battery (e.g., undesirable chemical changes). Examples of conductive materials include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0151] Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0.5wt% to about 5wt% of the conductive material.
[0152] Negative electrode current collector
[0153] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0154] Electrolyte
[0155] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.
[0156] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.
[0157] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0158] The nonaqueous organic solvent may be used alone or in a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used in a mixture, the mixing ratio may be suitably or appropriately adjusted according to desired or appropriate battery performance.
[0159] When the carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be used in combination, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0160] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.
[0161] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate and / or ethylene carbonate-based compounds to improve the battery cycle life.
[0162] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and / or cyanoethylene carbonate.
[0163] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures (eg, facilitates) the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of the lithium salt may include a lithium ion selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF6 、LiClO 4 、LiAlO 2 、LiAlCl 4 、LiPO 2 F 2 、LiCl、LiI、LiN(SO 3 C 2 F 5 ) 2 、Li(FSO 2 ) 2 N(lithium bis(fluorosulfonyl)imide; LiFSI), LiC 4 F 9 SO 3 、LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 )(wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0164] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently or appropriately moved.
[0165] Diaphragm
[0166] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof, and may include, for example, a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.
[0167] The separator may include a porous substrate and a coating on one or both surfaces (eg, opposite surfaces) of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.
[0168] The porous substrate may be a polymer film composed of any one (e.g., at least one) selected from the group consisting of polymer polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, polytetrafluoroethylene (Teflon), or may be a polymer film formed from a copolymer or mixture of two or more thereof.
[0169] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0170] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide; and a second structural unit, including at least one selected from a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid and / or its salt.
[0171] The inorganic material may include a 2 O 3 、SiO 2 、TiO 2 SnO 2 、CeO 2 , MgO, NiO, CaO, GaO, ZnO, ZrO 2 , Y 2 O 3 、SrTiO 3 、BaTiO 3 Mg(OH) 2 , boehmite and combinations thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0172] The organic material and the inorganic material may be mixed in one coating layer, or may exist in the form of a stack of a coating layer including an organic material and a coating layer including an inorganic material.
[0173] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0174] The following describes the embodiments and comparative examples of the present disclosure in more detail. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0175] Example 1
[0176] 1. Preparation of positive electrode active material
[0177] Ni 0.75 Mn 0.23 Al 0.02 (OH) 2 and LiOH in a molar ratio of 1:1.05, and then, a first heat treatment (e.g., a primary heat treatment) is performed at 845° C. in an oxygen atmosphere for 8 hours to prepare a layered lithium nickel manganese-based composite oxide in the form of secondary particles having Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 O 2 Composition and average particle size (D 50 ) is about 14μm.
[0178] A coating solution is prepared by adding aluminum sulfate and titanium sulfate and 600g of distilled water to a 1L reactor, and then stirring the mixture at about 350rpm for about 5 minutes to dissolve the salt. When the salt is completely dissolved, it is confirmed that the coating solution is colorless and transparent. Subsequently, 500g of layered lithium nickel manganese composite oxide is added to the coating solution being stirred for 1.5 minutes, and then, stirring is continued for about 30 minutes. In this article, aluminum sulfate is designed to have an aluminum content (e.g., amount) of 0.875mol% based on the total metal other than lithium in the final positive electrode active material of 100mol%, and titanium sulfate is designed to have a titanium content (e.g., amount) of 0.125mol% based on the total metal other than lithium in the final positive electrode active material of 100mol%. After completing stirring, the pH of its supernatant is 6.6.
[0179] After removing the solvent from the mixed solution by using an aspirator and a filter press, a coated product was obtained by vacuum drying at 190°C.
[0180] The coated product was subjected to a second heat treatment at 750° C. for 8 hours under an oxygen atmosphere to obtain a final positive electrode active material.
[0181] 2. Manufacturing of coin battery cells
[0182] 98.5 wt% of the positive electrode active material, 1.0 wt% of the polyvinylidene fluoride binder and 0.5 wt% of the carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, and the positive electrode active material layer slurry was coated on an aluminum foil current collector, and then dried and pressed to make a positive electrode. In this paper, the loading level of the positive electrode active material layer was 10 mg / cm 2 , and the density of the positive electrode active material layer in the final pressed positive electrode was about 3.4 g / cc.
[0183] Subsequently, the positive electrode was used together with lithium metal as a counter electrode and a polytetrafluoroethylene separator, and furthermore, an electrolyte (the electrolyte was prepared by mixing 1 M LiPF 6 The coin cell was prepared by dissolving in a mixed solvent of ethylene carbonate and dimethyl carbonate (the volume ratio of ethylene carbonate and dimethyl carbonate in the mixed solvent was 3:7) and manufacturing the coin cell by a conventional manufacturing method.
[0184] Example 2
[0185] The positive electrode active material and the coin cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (e.g., amount) of the aluminum sulfate was changed to 0.75 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material, and the titanium content (e.g., amount) of the titanium sulfate was changed to 0.25 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material.
[0186] Comparative Example 1
[0187] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Example 1, except that the Al and Ti coating was not performed and the lithium nickel manganese-based composite oxide itself was used as the positive electrode active material.
[0188] Comparative Example 2
[0189] A positive electrode active material and a coin cell are manufactured in substantially the same manner as in Example 1, except that only Al coating is performed (provided) without Ti coating by changing the aluminum content (e.g., amount) in aluminum sulfate to 0.8 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material.
[0190] Comparative Example 3
[0191] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Comparative Example 2, except that the aluminum content (eg, amount) in aluminum sulfate was changed to 1.0 mol %.
[0192] Comparative Example 4
[0193] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Comparative Example 2, except that the aluminum content (eg, amount) in aluminum sulfate was changed to 1.2 mol %.
[0194] Comparative Example 5
[0195] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Comparative Example 2, except that the aluminum content (eg, amount) in aluminum sulfate was changed to 1.5 mol %.
[0196] Comparative Example 6
[0197] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Example 1, except that Ti coating was performed instead of Al coating, and wherein the titanium content (e.g., amount) in the titanium raw material was changed to 0.25 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material.
[0198] Comparative Example 7
[0199] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Comparative Example 6, except that the titanium content (eg, amount) in the titanium raw material was changed to 0.5 mol % based on 100 mol % of total metals other than lithium in the final positive electrode active material.
[0200] Comparative Example 8
[0201] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Comparative Example 6, except that the titanium content (eg, amount) in the titanium raw material was changed to 1.0 mol % based on 100 mol % of total metals other than lithium in the final positive electrode active material.
[0202] Comparative Example 9
[0203] A positive electrode active material and a coin cell were manufactured in substantially the same manner as in Example 1, except that the aluminum content (e.g., amount) of aluminum sulfate was changed to 0.5 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material, and the titanium content (e.g., amount) of titanium sulfate was changed to 0.5 mol% based on 100 mol% of the total metals other than lithium in the final positive electrode active material.
[0204] Evaluation Example 1: SEM Analysis
[0205] Figure 5 is a SEM image of the surface of the coated product prepared in Example 1, Figure 6 To highlight Figure 5 EDS analysis image of Al element in Figure 7 To highlight Figure 5 EDS analysis image of Ti element in Figure 5 In the figure, it can be seen that a spider web-shaped coating is formed on the surface of the secondary particles. Figure 6 In the figure, it can be seen that Al is detected in a distribution similar to the spider web shape, and in Figure 7 In the graph, it can be seen that Ti is detected in a part of the Al distribution area.
[0206] Figure 8 is a SEM image of the surface of the coating product prepared in Example 1, Fig. 9 To highlight Figure 8 EDS analysis image of the Al element in the white square area, and Fig.10 To highlight Figure 8 EDS analysis image of the Ti element in the white square area. Fig.11 for Figure 8 to Figure 10 EDS analysis of the region 2 marked in Figure 2. Fig.11 , Al peaks and Ti peaks were detected on the surface of secondary particles.
[0207] Fig.12 is a SEM image of the surface of the final positive electrode active material prepared in Example 1, and Fig.13 Enlarge the image. Fig.14 is a SEM image of the surface of the final positive electrode active material prepared in Comparative Example 1, and Fig.15 Enlarge the image. Fig.12 and Fig.13 Compared with Example 1, Fig.14 and Fig.15 Comparative Example 1 exhibits a smooth secondary particle surface, however, Fig.12 and Fig.13 Example 1 shows a coating containing Al found on the surface of secondary particles.
[0208] Evaluation Example 2: XPS Analysis
[0209] XPS analysis was performed under the following analysis conditions by using an ESCALAB 250Xi instrument manufactured by Thermo Fisher Scientific.
[0210] -X-ray: Al Ka 1486.6eV
[0211] - Charge neutralization: low energy ions and electrons
[0212] -Ar + Gun: 4000eV
[0213] -Ar + Single atomic gun
[0214] As the XPS analysis result of the surface of the final positive electrode active material of Example 1, Fig.16 As shown in , Al components were detected, and Fig.17 As shown in , Ti component was detected. In addition, the XPS depth distribution of the final positive electrode active material of Example 1 was analyzed, and the results are as follows Fig.18 shown in and Fig.19 , Al element distribution and Ti element distribution are shown.
[0215] refer to Fig.18 and Fig.19 , it can be concluded that, without being bound by any particular theory, Al and Ti exist on the surface of the secondary particles of the positive electrode active material, but the Al and Ti contents decrease from the surface to the inside, wherein the graphs of the Al and Ti contents have similar decreasing shapes (e.g., graphs showing a decrease in Al content and a decrease in Ti content have similar shapes). In one or more embodiments, on the surface of the secondary particles of the positive electrode active material, the Al content (e.g., amount) is about 5 atomic percent (at%) to 20 at%, and the Ti content (e.g., amount) is about 0.5 at% to 2 at%, based on 100 at% of the total elements on the surface of the positive electrode active material.
[0216] Evaluation Example 3: Evaluation of initial charge / discharge capacity and efficiency of batteries and high-temperature cycle life characteristics
[0217] The coin cells of Examples 1, 2 and Comparative Examples 1 to 9 were charged at a constant current of 0.2C to an upper limit voltage of 4.45V, and charged to 0.05C at a constant voltage, and then discharged at 0.2C to a cutoff voltage of 3.0V at 25°C to perform initial charging and discharging. In Table 1, the initial charging capacity (i.e., "0.2C charging" in Table 1), the initial discharging capacity (i.e., "0.2C discharging" in Table 1), and the ratio of the initial discharging capacity to the initial charging capacity (i.e., "efficiency" in Table 1) are provided.
[0218] Subsequently, the battery cell was repeatedly charged and discharged at 1.0C for 50 or more times within a voltage range of 3.0V to 4.45V at 45°C to calculate the ratio of the discharge capacity at the 50th cycle to the initial discharge capacity, which is shown as “High Temperature Cycle Life” in Table 1.
[0219] Table 1
[0220]
[0221] Referring to Table 1, Examples 1 and 2 each simultaneously (e.g., synchronously) achieve appropriately high (or improved) initial charge and discharge capacity, appropriately high (or improved) initial charge and discharge efficiency, and excellent or improved high temperature cycle life characteristics compared to the comparative example. That is, compared to Comparative Example 3 in which only 1.0 mol% of Al is coated, Example 1 exhibits improved initial discharge capacity, initial charge and discharge efficiency, and high temperature cycle life characteristics, and compared to Comparative Example 3, Example 2 exhibits significantly improved high temperature cycle life characteristics.
[0222] Compared to the example embodiments (e.g., Examples 1 and 2), Comparative Example 1 in which a coating layer containing Al and Ti was not introduced exhibited poor high temperature cycle life characteristics, and Comparative Examples 2 and 3 in which only Al was coated in an amount of 0.8 mol% and 1.0 mol%, respectively, each exhibited slightly (e.g., slightly) deteriorated high temperature cycle life characteristics. Comparative Examples 4 and 5 in which only Al was coated in an amount of 1.2 mol% and 1.5 mol%, respectively, each exhibited significantly deteriorated high temperature cycle life characteristics. Compared to Examples 1 and 2, Comparative Examples 6 to 8 in which only Ti was coated without Al coating each exhibited significantly lower initial discharge capacity and initial charge and discharge efficiency, and Comparative Example 8 in which only Ti was coated in an amount of 1.0 mol% exhibited significantly deteriorated high temperature cycle life characteristics. Further, Comparative Example 9, in which the ratio of the Al content (e.g., amount) of the coating layer to the Ti content (e.g., amount) of the coating layer was 1, exhibited slightly deteriorated initial discharge capacity, initial charge and discharge efficiency, and high-temperature cycle life characteristics, while the example embodiments (i.e., Examples 1, 2) each of which had a ratio of the Al content to the Ti content (Al:Ti) of 2 or more exhibited significantly improved battery performance.
[0223] Although the present disclosure has been described in conjunction with what are presently considered to be example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments. Instead, it is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material comprising: a plurality of core particles comprising a layered lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of total metals other than lithium in the layered lithium nickel manganese-based composite oxide, and A coating layer is disposed on a surface of each of the plurality of core particles, the coating layer comprising Al and Ti.
2. The positive electrode active material according to claim 1, wherein On the surface of the positive electrode active material, a ratio of the Al content to the Ti content is greater than or equal to 2.
3. The positive electrode active material according to claim 1, wherein The Al content is 5 to 35 at %, and the Ti content is 0.1 to 3.0 at %, based on 100 at % of total elements on the surface of the positive electrode active material, as measured by X-ray photoelectron spectroscopy.
4. The positive electrode active material according to claim 1, wherein The Al content is 5 to 25 at %, and the Ti content is 0.5 to 2.0 at %, based on 100 at % of total elements on the surface of the positive electrode active material as measured by X-ray photoelectron spectroscopy.
5. The positive electrode active material according to claim 1, wherein The coating layer may have an Al content of 0.1 mol% to 3.0 mol% and a Ti content of 0.01 mol% to 1.5 mol% based on 100 mol% of total metals except lithium in the positive electrode active material.
6. The positive electrode active material according to claim 1, wherein The coating layer may have an Al content of 0.5 mol% to 1.5 mol% and a Ti content of 0.01 mol% to 1.0 mol% based on 100 mol% of total metals except lithium in the positive electrode active material.
7. The positive electrode active material according to claim 1, wherein The total amount of Al and Ti in the coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material.
8. The positive electrode active material according to claim 1, wherein The coating layer is in the form of a shell continuously surrounding the surface of each of the plurality of core particles.
9. The positive electrode active material according to claim 1, wherein The coating has a thickness of 5 nm to 200 nm, and The positive electrode active material is in the form of a plurality of positive electrode active material particles, and a deviation in thickness of the coating layer within a positive electrode active material particle among the plurality of positive electrode active material particles is less than or equal to 20%.
10. The positive electrode active material according to claim 1, wherein The coating comprises a layered aluminum compound, and The coating further includes nickel, manganese, or a combination thereof.
11. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide of the multiple core particles, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the nickel content is 60 mol% to 80 mol%, the manganese content is greater than or equal to 10 mol%, and the cobalt content is 0 mol% to 0.01 mol%.
12. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese-based composite oxide of the plurality of core particles further comprises aluminum, and the aluminum content in the plurality of core particles is greater than 0 mol% and less than or equal to 3 mol%, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese-based composite oxide, and / or The concentration of aluminum in the plurality of core particles is substantially uniform.
13. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese-based composite oxide of the plurality of core particles is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 , In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more selected from F, P and S, and wherein each of the plurality of core particles is in the form of a secondary particle formed by aggregating a plurality of primary particles, and The average particle size D of the positive electrode active material in the form of a plurality of positive electrode active material particles 50 The positive electrode active material particles include a plurality of core particles and the coating layer on the surface of each of the plurality of core particles.
14. A method for preparing a positive electrode active material, the method comprising: preparing a plurality of core particles, the plurality of core particles comprising a layered lithium nickel manganese-based composite oxide, the layered lithium nickel manganese-based composite oxide having a nickel content greater than or equal to 60 mol % based on 100 mol % of total metals other than lithium in the layered lithium nickel manganese-based composite oxide, adding an aluminum raw material and a titanium raw material to an aqueous solvent and mixing to prepare a coating solution, adding a plurality of core particles to the coating solution and mixing to prepare a mixed solution, and The aqueous solvent is removed from the mixed solution, and the resultant is dried and heat-treated to obtain a positive electrode active material.
15. The method of claim 14, wherein In the layered lithium nickel manganese composite oxide, based on 100 mol% of the total metals other than lithium in the layered lithium nickel manganese composite oxide, the nickel content is 60 mol% to 80 mol%, the manganese content is greater than or equal to 10 mol%, the aluminum content is 0 mol% to 3 mol%, and the cobalt content is 0 mol% to 0.01 mol%; and / or wherein the aluminum raw material is aluminum sulfate, and the titanium raw material is titanium sulfate, titanium nitrate or a combination thereof; and / or The aluminum raw material has an aluminum content of 0.1 mol% to 3.0 mol% and the titanium raw material has a titanium content of 0.01 mol% to 1.5 mol% based on 100 mol% of the total metals except lithium in the positive electrode active material.
16. The method of claim 14, wherein The aluminum raw material and the titanium raw material are added to the aqueous solvent and mixed at 100 rpm to 800 rpm for 1 minute to 60 minutes. The adding of the plurality of core particles to the coating solution is performed at 30 seconds / 500 g to 2 minutes / 500 g, After adding the plurality of core particles, mixing the plurality of core particles with the coating solution is performed for 15 minutes to 60 minutes, and / or After the plurality of core particles are mixed with the coating solution, the pH of the supernatant thereof is 5.5 to 8.
5.
17. The method of claim 14, wherein After removing the aqueous solvent from the mixed solution, the obtained product is dried under vacuum at 40° C. to 240° C., and / or The heat treatment is performed in a temperature range of 730°C to 800°C.
18. The method of claim 14, wherein After removing the aqueous solvent from the mixed solution and drying the obtained product, the dried obtained product comprises: multiple nuclear granules; and a coating layer on a surface of each of the plurality of core particles and including Al and Ti, wherein the coating layer has a spider web shape.
19. A positive electrode comprising: a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 13 or the positive electrode active material prepared by the method according to any one of claims 14 to 18, The positive electrode active material layer has a 10 mg / cm 2 ~40mg / cm 2 The load level, and / or The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.
20. A rechargeable lithium battery comprising: The positive electrode according to claim 19, negative electrode, and Electrolyte, The charging upper limit voltage of the rechargeable lithium battery is greater than or equal to 4.45V.